Associação entre bem-estar psicossocial, religiosidade e espiritualidade em pacientes com sequelas aparentes de cirurgia oncológica na região de cabeça e pescoço - Reis, Liliane Braga Monteiro dos (2016)
Treatment of cancer located in the head and neck region includes different therapeutic interventions according to the staging of the tumor, and the surgical approach may culminate in considerable sequelae and biopsychosocial changes in individuals. The objective of this study was to investigate the association between psychosocial well-being and religiosity / spirituality in patients with apparent sequelae of oncologic surgery in the head and neck region. A crosssectional study was conducted in 202 adults at a referral center for cancer treatment in the Midwest Brazil. Sociodemographic, health and health related behavious and psychosocial data were collected through interviews, clinical exams and search of medical records. The variables related to psychosocial well-being were: quality of life (QOL), using the Functional Assessment of Cancer Therapy Head and Neck (FACT-HN) and the University of Washington Quality of Life Questionnaire for patients with head and neck cancer (UW-QOL); and self-perception of appearance, assessed by the Derriford Appearance Scale 24 (DAS24). The explanatory independent variables were: religiosity, evaluated through the Duke University's Index of Religiosity (DUREL) and spirituality, with the Functional Assessment of Chronic Illness TherapySpiritual Well-Being Scale (FACIT-Sp12). Data were analyzed using the Chi-square test and Poisson regression with robust variance. The mean QOL score (FACT-HN) was 97.9 (SD=20.1) and the QOL (UW-QOL) was 744.6 (SD=228.0). The mean total self-perception score was 36.0 (SD=11.7). Religiousness had a mean score of 21.6 (SD=5.0) and spirituality 35.5 (SD=7.5). In the bivariate analyzes, the variables religiousness and spirituality were individually associated with the QOL evaluated by the FACT-HN instrument, while only religiosity was associated with the QV evaluated by the UW-QOL and only spirituality was associated with self-perception of appearance. In the final model of Poisson regression, after adjusting for clinical, sociodemographic characteristics and health behaviors, the variables associated with high QOL (FACT-HN) were: high religiosity and spirituality, male sex and surgery time equal to or greater than two years. Those associated with high QV (UW-QOL) were: high religiosity, cancer sites except oral cavity and oropharynx, types of cancer except squamous cell and basal cell, site of sequelae except the lower / cervical thirds and only surgery as treatment. The variables associated with the best self-perception of appearance were high spirituality, stage T of the lesion (T1+T2), cancer site except oropharynx and only surgery as treatment. It was concluded that there is an association between QOL, religiosity and spirituality and between self-perception of appearance and spirituality, regardless of sociodemographic variables, clinical conditions and health behaviors.